Preparation and Characterization of Polyelectrolyte Complexes of Hibiscus esculentus (Okra) Gum and Chitosan - Vivekjot Brar; Gurpreet Kaur (International Journal of Biomaterials)
Polyelectrolyte complexes (PECs) of Okra gum (OKG) extracted from fruits of Hibiscus esculentus (Malvaceae) and chitosan (CH) were prepared using ionic gelation technique. The PECs were insoluble and maximum yield was obtained at weight ratio of 7 : 3. The supernatant obtained after extracting PECs was clearly representing complete conversion of polysaccharides into PECs. Complexation was also evaluated by measuring the viscosity of supernatant after precipitation of PECs. The dried PECs were characterized using FTIR, DSC, zeta potential, water uptake, and SEM studies. Thermal analysis of PECs prepared at all ratios (10 : 90, 20 : 80, 30 : 70, 40 : 60, 50 : 50, 60 : 40, 70 : 30, 80 : 20, and 90 : 10; OKG : CH) depicted an endothermic peak at approximately 240°C representing cleavage of electrostatic bond between OKG and CH. The optimized ratio (7 : 3) exhibited a zeta potential of −0.434 mV and displayed a porous structure in SEM analysis. These OKG-CH PECs can be further employed as promising carrier for drug delivery.